Radio frequency identification based materials tracking system for construction industry - Jain, Sameer; Sanchez, Gustavo; Sunil, Taruna; Sharma, Dinesh Kumar (Institute of Advanced Engineering and Science, 2024)
The construction industry is an industry that is always surrounded by uncertainties and risks. The industry is always associated with a threatindustry which has a complex, tedious layout and techniques characterized by unpredictable circumstances. It comprises a variety of human talents and the coordination of different areas and activities associated with it. In this competitive era of the construction industry, delays and cost overruns of the project are often common in every project and the causes of that are also common. One of the problems which we are trying to cater to is the improper handling of materials at the construction site. In this paper, we propose developing a system that is capable of tracking construction material on site that would benefit the contractor and client for better control over inventory on-site and to minimize loss of material that occurs due to theft and misplacing of materials.